Outbreak of a new coronavirus (SARS-CoV-2) infection and pollen exposure - Awaya, Akira; Kuroiwa, Yoshiyuki (Archives of Community Medicine and Public Health, 2021)
The inference that this paper points out is that the stimulating environmental factor behind why the SARS-CoV-2 epidemic occurred in Wuhan is probably pollen from the plant kingdom. We started in 2003 to point out the epidemiological fact that Kawasaki disease is probably a Pollen-Induced Disease (PID) triggered by pollen exposure. Subsequently, we also examined the correlation analysis between the cyclical changes in pollen count and the changes in the number of new patients with respect to the incidence of 40 designated intractable diseases and 24 cancers and malignancies over a 40-year period, and were able to show a significant association. Since the 1990s, it has been reported that the number of pollen scattered in Wuhan, China is far higher than the number of pollen scattered in other parts of Japan, and is by far the highest in China. Before the COVID-19 epidemic began, it is conceivable that some of the allergic prone (allergic constitution) residents of Wuhan City, who have been exposed to large amounts of pollen in the spring and small amounts of precursor pollen in the fall each year, fell into a compromised immune state in November. Through a mechanism similar to the initial process of carcinogenesis triggered by pollen exposure, patients infected with the old coronavirus, which is a foreign substance, are thought to have developed a mechanism whereby the old coronavirus mutates (becomes highly toxic) in the host body in the course of their biological response to the virus. This supposed host response process (trick) allows the virus to expand its mutation at the genetic level, which is beyond the control of the host human, during the replication process. As a result, the virus will cause a situation (condition) that will lead to an infectious disease pandemic that can be transmitted from person to person who have not yet developed resistance. It is implied that within the host, a suicidal pathological process, costly to humanity, may be occurring in a process similar to that of individual carcinogenesis.